Trophic State of the Pekak Lake, Siak Hulu District, Kampar Regency Based on Trophic State Index - Dio M Silalahi; Madju Siagian; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTMany activities in the Pekak Lake contribute the input of organic and anorganic matter that affects the water quality, especially nutrient concentration in waters. A research aims to understand the trophic state of the Pekak Lake based on TSI has been conducted in March-April 2018. There were 3 stations, namely in the inlet, midle part of the lake and the end area of the lake. In each station, there are 2 sampling points, in the surface (0.2 m) and 2 Secchi depth (0.75 m). Sampling were conducted 3 times, once/week. Water quality parameters measured were total phosphate, chlorophyll-a, transparancy, dissolved oxygen, CO2,pH and temperature. Results shown that the total phospate was 0.152-0.508 mg/L, chlorophyll-a 7.061-11.186 µg/L, transparency: 0.69-0.77 m, dissolved oxygen: 5.36-5.96 mg/L, CO2:8.81-16 mg/L, pH: 5, temperature: 27-30oC and TSI (Trophic State Index) value: 64.559-70.465. Based on TSI, the Pekak Lake can be categorized as moderate eutrophic-hypereutrophic.Keywords: Kampar River, Eutrophic-hypereurophic, Oxbow Lake, TSI